Quality of health care in Primary Care: perspective of people with Diabetes Mellitus - Rosilene Rocha Palasson; Elisabete Pimenta Araújo Paz; Gerson Luiz Marinho; Luiz Felipe da Silva Pinto; Elen Ferraz Teston; Margareth de Almeida Gomes; Maria Helena do Nascimento Souza; Sonia Silva Marcon (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to identify how people with diabetes assess the care offered by Primary Care teams. Methods: a cross-sectional study based on structured interviews with the application of the Patient Assessment of Chronic Illness instrument to people with Type 2 Diabetes Mellitus. Data were submitted to statistical analysis. Results: 451 individuals participated in the study, more than half aged 60 years or older (64.0%); 63.9% had been diagnosed for more than five years; and 23.9% used insulin. The average score obtained was 2.5, which indicated little involvement in self-care and low support for the care of the chronic condition by the Family Health Strategy team, and was higher among women and people with a partner. Conclusions: people with diabetes consider that they do not receive individualized treatment, with dialogue and discussion for setting goals, and that they are not prepared for self-managing their health condition.